Effect of thermal processing methods on the eating qualities and acceptability of different meat types (2017)
This study was carried out to evaluate the eating qualities of six different meat types namely: beef, chevon, pork, rabbit, turkey and chicken cooked with three methods. The three cooking methods employed were frying, boiling and roasting. Fresh meat cuts (250g) of 5 meat types were purchased from Ayetoro market in Yewa North Local Government areas of Ogun State, while live rabbits were bought and slaughtered and 250g of meat harvested and used for this study. The 250g of each meat type was divided into 50g and subjected to cooking using frying, boiling and roasting for 20 minutes. The meat samples were served to a semi-trained 10-member taste panel that adjudged the test on the meats for flavour, tenderness, juiciness, texture and overall acceptability using 9-point hedonic scale on which 1= disliked extremely and 9= liked extremely. The results showed that frying increased (p<0.05) the . juiciness and texture of rabbit, turkey, chicken and pork meats as well as the overall acceptability of the same meat types. Boiling increased the flavour of beef and chevon and tenderness of rabbit, turkey, pork and chicken as well as the texture of beef, chevon, pork and rabbit, but enhanced the overall acceptability of beef and chevon. Roasting improved the flavour of beef and chevon, tenderized pork and rabbit meat as well as increased the juiciness of beef and chevon, texture of beef, chevon and rabbit meats; it increased the consumer’s acceptability of beef, chevon and rabbit meats. It was concluded that each meat type should be cooked based on the method that impacts palatability quality which the consumer desired. It was suggested that pork, rabbit, turkey and chicken meats be fried as it enhanced most of the palatability qualities of these meat types, beef and chevon meat be boiled or roasted for higher acceptability.